Analisis strategi pemasaran UMKM menggunakan pendekatan kualitatif fenomenologi dalam era MEA - Reza Heriyoga; Basuki Rachmat (Journal of Business & Banking, 2015)
The purpose of this research was to find out and describe how the application of the mar-keting strategy is, in developing the micro small medium enterprise, in the face of ASEAN Economic Community (AEC) 2015. The study was focusing on the micro SMEs of handicraft industries e.g. leather, bags, and suitcases in Tanggulangin-Sidoarjo. The method employed in this study was the phenomenology of qualitative ap-proach. The data were collected from the owners of micro and small management, con-sumers, with the total number of 5 people and 1 from the government. It used observa-tion, documentation, and structured interview with the open questions for getting com-plete information. The results showed that the marketing strategy of the micro SME’s consisting of product, price, promotion, and distribution was not yet going well for fac-ing the ASEAN economic community 2015. In terms of products and the price, they were good but in terms of distribution and promotion, they were very weak. Other re-sults of the local government related to the condition of being still in half-measures in the development of the micro SMEs, especially in terms of the promotion and the awarding business credit.